DAMPAK PEMBELAJARA DARING TERHADAP KUALITAS BELAJAR BAGI SISWA MAN 2 MALUKU TENGAH - Holle, Muhammad Ali (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2023)
This article describes the impact of online learning on the quality of learning for students at MAN 2 Central Maluku. The purpose of the study was to determine the role of educators in online learning at MAN 2 Central Maluku, the quality of online learning at MAN 2 Central Maluku, and barriers to online learning at MAN 2 Central Maluku. This type of research is descriptive qualitative. Data collection methods used are observation, interviews and documentation. The data obtained were then analyzed descriptively using swot analysis. The results of the study show that: a) The role of teachers at MAN 2 Central Maluku is very good, teachers work professionally and according to their scientific competence, this can be seen from the teacher's efforts in anticipating online learning methods with various trainings to prepare professional teachers in answering educational problems. b) The quality of online learning is still not maximized due to supervision and learning outcomes that are not optimal, besides that online teacher learning methods are also not effective which makes students more saturated, learning should improve students' understanding and skills. c) The obstacles during the Covid-19 pandemic are certainly very many because the online learning process requires schools, teachers and parents to be ready, otherwise there will be an impression of being forced, this will be a big problem for the quality of Indonesian education in the future